The Influence of Speed, Agility and Balance on Dribbling Ability in Football Games - Pahruddin, Fikram Anriawan; Syahruddin, Syahruddin; Bismar, Ahmad Rum; Ihsan, Andi; Hudain, Muh. Adnan (Indonesian Journal of Sport Management, 2024)
This research aims to determine the effect of speed (KL), agility (KLC) and balance (KSB) on ball dribbling ability (KMB) in the game. This research is ex post facto research, which is correlational and uses a path analysis research design (Path Analysis) with the exogenous variables speed (X1), agility (X2), and balance (X3), while the endogenous is the ability to dribble the ball (Y). The population used was all SMA Negeri 3 Luwu students who participated in football extracurricular activities, with a sample size of 25 students. The test instruments used were the 30-meter running speed test with a validity of 0.884 and a reliability of 0.991, a dodging run agility test with a validity of 0.82 and a reliability of 0.93, a dynamic balance test with a validity of 0.298 and a reliability of 0.734, a ball dribbling skills test with a validity of 0.700 and a reliability of 0.818. The data analysis technique used is descriptive analysis and path analysis with the help of the SPSS version 25 computer program with a significance level of 95% or α = 0.05. The data analysis method applied includes descriptive and path analysis using SPSS version 25 computer software, with a significance level of 95% or α = 0.05. The research results show that 1) There is an influence of KL on KSB (p<0.024.2) There is an influence of KLC on KSB (p<0.000), 3) There is an influence of KL on KMB (p<0.048), 4) There is an influence of KLC on KMB (p< 0.000), 5) There is an influence of KSB on KMB (p<0.028). 6) There is an influence of KL on KMB through KSB (p<0.000). 7) There is an influence of KLC on KMB through KSB (p<0.000).